The Late Effects of Anticancer Therapy after Childhood Wilm's Tumor: The Role of Diastolic Function and Ambulatory Blood Pressure Monitoring - Elli, M.; Sungur, M.; Genç, G.; Ayyildiz, P.; Daǧdemir, A.; Pinarli, F.G.; Acar, S. (Oxford Univ Press, 2013)
Objective: Wilms' tumor, or nephroblastoma, is the most common primary malignant renal tumor of childhood. The excellent outcome now expected for most children with this tumor is attributed to the combination of effective adjuvant chemotherapy, improved surgical and anesthetic techniques and also the radiosensitivity of the tumor. The numerous organ systems are subject to the late effects of anticancer therapy. The aim of this study was to investigate the blood pressure profile and ambulatory blood pressure monitoring, and also cardiac diastolic functions and pulmonary venous flow in 25 children with unilateralWilms' tumor in remission. Methods: The patient group consists of 25 patients who successfully completed anticancer treatment for unilateral Wilms' tumor. Thirty-three age-, weight- and height-matched healthy children were considered as a control group for an echocardiographic study. Also, 20 age-, weight- and height-matched healthy children were considered as a control group for the ambulatory blood pressure monitoring study. Results: In our study, 24 h, daytime and night-time systolic blood pressure and night-time diastolic blood pressure measurements were found to be significantly increased in the patient group compared with healthy children. We detected diastolic filling pattern abnormalities. We also found increase in pulmonary venous flow (systolic and diastolic) inWilms' tumor group. Conclusions: We suggest the regular follow-up of survivors of Wilms' tumor for care and prevention of cardiovascular diseases.©The Author 2013.
Keywords: Ambulatory Blood Pressure Monitoring; Diastolic Functions; Late Effects; Pulmonary Venous Flow; Wilms' Tumor